(untitled) (Biological Sciences - PJSIR, 2005)
Clotting time of blood samples drawn from eight patients was determined using three variants of plant extracts (crude, aqueous and chloroform) of the leaf of Bryophyllum pinnatum. These extracts clotted the test blood samples faster than the untreated blood samples, which ranged between 0.34-3.27 min. Blood samples pretreated with heparin (antico- agulant) did not clot, to any extent, when treated with the B. pinnatum extracts. All the test blood samples showed different clotting times. The clotting efficiency of the different extracts was crude > aqueous > chloroform > control. The clotting time for different test blood samples, not treated with any variant of the plant extracts (control samples), ranged between 10.363±0.012 and 14.483±0.008 (min). Normal blood clotting time is between 6-10 min, which may indicate deficiencies in one or more clotting factors in the untreated test blood samples drawn from the study subjects.